Sugar content of selected Malaysian desserts, snacks and cooked foods commonly consumed by Malaysian older adults - Ching, Phang Chong; Suzana Shahar; Hasnah Haron; Mohd Fairulnizal Md Noh (Penerbit Universiti Kebangsaan Malaysia, 2018)
Excess added sugar consumption is related to poor health outcomes in older adults. The sugar content of local food is limited. However, this information is imperative for understanding potential risks from overconsumption of sugars among older adults. This study was carried out to determine the type and total sugar contents in 70 types of local desserts, snacks and cooked foods, using high performance liquid chromatography. The type of food chosen was based on the highly consumed food by the older adults in Malaysia. The samples were collected in triplicates from local restaurants or stalls located in Selangor, Perak and Johor, stored at -20°C and freeze dried prior to analysis. Results showed that average sugar in each 100 g of local desserts, snacks and cooked foods were 13.69 ± 5.94 g, 8.41 ± 6.15 g and 2.1 ± 1.87 g respectively. The highest sugar content per 100 g samples was found to be in sweet potato donut (kuih keria), mashed banana fritter (cekodok pisang) and noodles with sweet potato gravy (mee rebus). The lowest sugar content per 100 g samples was found to be baked glutinous rice (pulut panggang), vadai and noodle soup (mee sup). Meanwhile, the highest sugar content per standard portion was found to be noodles with sweet potato gravy (mee rebus), peanut pancake (kuih apam balik) and banana savoury (pengat pisang). Percentage of recovery for the sugar analysis was 95.2 ± 6.8%. The main type of sugar found in this analysed food samples was sucrose followed by maltose, glucose, fructose and lactose. Sucrose was the most common added sugars in local desserts, snacks and cooked foods of this study. However, compliance with low added sugar recommendations may not be achievable for the general public. Thus, these findings can be utilised in raising public awareness and assist in better estimation of sugar contents and intake.